Evaluating the effects of simulated microgravity on mouse fibroblast - Son, Hoang Nghia; Huy, Hoang Nguyen Quang; Tram, Tran Thi Bich; Cang, Ly Ngoc; Chi, Ho Nguyen Quynh; Dai, Truong Xuan; Thanh, Le Ngoc Phuong; Han, Truong Thi; Han, Nguyen Thai Minh; Long, Le Thanh (Academia Journal of Biology, 2020)
The present study investigated how mouse fibroblasts changed under microgravity (SMG) conditions (< 10-3 G) simulated by 3D clinostat. Results showed that SMG condition markedly reduced the proliferation of mouse fibroblasts, significantly reducing the nuclear area and intensity. Compared to the control group, the mouse fibroblasts ratio of the SMG group was higher in the G0/G1 phase but lower in the S phase and G2/M phase. The ratios of early and late apoptotic cells were also higher in the SMG group. The mouse fibroblasts under SMG conditions exhibited a reduction of β-Actin and α-Tubulin 3 expressions compared to the control group. These results suggested that the SMG condition diminished the proliferation and downregulated cytoskeletal protein expression of mouse fibroblasts.